The Importance of Proper Oxygenation in 3D Culture - Tse, Hubert M.; Gardner, Graeme; Dominguez-Bendala, Juan; Fraker, Christopher A. (Frontiers in Bioengineering and Biotechnology, 2021)
Cell culture typically employs inexpensive, disposable plasticware and standard humidified CO2/room air incubators (5% CO2, ~20% oxygen). These methods have historically proven adequate for the maintenance of viability, function and proliferation of many cell types, but with broad variation in culture practices. With technological advances it is becoming increasingly clear that cell culture is not a “one size fits all” procedure. Recently, there is a shift towards comprehension of the individual physiological niches of cultured cells. As scale-up production of single cell and 3D aggregates for therapeutic applications has expanded, researchers have focused on understanding the role of many environmental metabolites/forces on cell function and viability. Oxygen, due to its role in cell processes and the urgent cellular requirement for adequate supply to maintain critical energy generation, is one such metabolite gaining increased focus. With the advent of improved oxygen sensing technologies and computational predictive modeling, it is becoming evident that parameters such as cell seeding density, culture media height, cellular oxygen consumption rate and aggregate dimensions should be considered for experimental reproducibility. In this review, we will examine the role of oxygen in 3D cell culture with particular emphasis on primary islets of Langerhans and stem cell-derived insulin-producing SC- cells, both known for their high metabolic demands. We will implement finite element modeling to simulate historical and current culture methods in referenced manuscripts and innovations focusing on oxygen distribution. Our group and others have shown that oxygen plays a key role in proliferation, differentiation and function of these 3D aggregates. Their culture in plastic consistently results in core regions of hypoxia/anoxia exacerbated by increased media height, aggregate dimensions and oxygen consumption rates. Static gas permeable systems ameliorate this problem. The use of rotational culture and other dynamic culture systems also have advantages in terms of oxygen supply but come with the caveat that these endocrine aggregates are also exquisitely sensitive to mechanical perturbation. As recent work demonstrates, there is a strong rationale for the use of alternate in vitro systems to maintain physio-normal environments for cell growth and function for better phenotypic approximation of in vivo counterparts.